دراسة تحليلية لتأثير الزلازل في السدود الركامية بطريقة العناصر المنتهية دراسة حالة: سد الباسل/ طرطوس - حسن عز الدين; حسن مالك; الأسعد همام (Latakia University Journal -Engineering Sciences Series, 2017)
يتضمن البحث دراسة تحليلية بطريقة العناصر المنتهية لتأثير الزلازل في استقرار سد الباسل،لذلك قمنا بوضع نموذج عددي مناسب بالاستعانة ببرنامجيQuake/W, Slope/W . بعد تشغيل النموذج حصلنا على نتائج المحاكاة والتي تلخصت في حساب معاملات الأمان من أجل التحقق من الاستقرار النهائي للسد تحت تأثير زلازل مختلفة الشدة، ومن ثم أجريت مقارنة بين الحالتين الستاتيكية والديناميكية للنموذج تبين تأثير متغيرات القص للتربة كزاوية الاحتكاك الداخلي وتأثير ميول منحدري السد وحالات مناسيب المياه المختلفة للبحيرة وارتفاع السد بالإضافة إلى تأثير مادة الإنشاء على استقرار جسم السد،وبعد دراسة كل حالة تبعاً للبارامترات التي يتم إدخالها، وبناء على معاملات الأمان الناتجة رُسمت مخططات بيانية تظهر الأثر الإيجابي أو السلبي لزيادة أو نقصان أي متغير من متغيرات السد الركامي وذلك في كل من الحالتين الستاتيكية والديناميكية،وبعد ذلك قمنا بدراسة تأثير التضخم الزلزالي الناجم عن جسم السد على كل من المركبتين الأفقية والشاقولية للتسارع الزلزالي. وتساعدنا النتائج في الاختيار الأمثل لمتغيرات السد الركامي عند التصميم. This research includes analytical study by Finite Element Method about the effect of earthquakes in the stability of ALBASEL DAM, so we have set a numerical model suitable by using programs Slope/W, Quake/W. We run the model and we got the results of the simulation, which summarized in calculation factors of safety for verification the final stability of the dam under the effect of different intensity earthquakes. And then were compared between the two cases static and dynamic model showing the effect of the shear variables of the soil angle of internal friction and tendency of slops dam and the different situations of the lake water levels and the high of dam in addition to the effect of the construction material of the dam on the stability of the body of the dam. After the study each case depending on the parameters, that are entered, and based on the resulting factors of safety, the diagrams are painted to appear the positive or the negative effects to increase or decrease any variable of the dam variables in each of the static case and the dynamic case. And then we studied the effect of seismic Amplification resulting from the body of the dam on both the two horizontal and vertical component of seismic acceleration. The results will help us in a perfect choice for variables of Embankment dams for design.